2007
DOI: 10.1111/j.1600-0846.2007.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Dye exclusion as a means to measure wetness protection of human skin

Abstract: The dye exclusion method was able to demonstrate the advantage of barrier ointments for wetness protection and also to discriminate between ointment formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
0
3
0
5
Order By: Relevance
“…30 A significantly lower value in Chroma Meter reading was measured in patients with untreated AD after 10 hours compared with that seen at time point zero, indicating a significant dye penetration caused by a disrupted outside-inside barrier. Dye penetration was significantly reduced by betamethasone and even more so by pimecrolimus treatment compared with that seen in untreated control skin.…”
Section: Tewl and Dye Penetrationmentioning
confidence: 82%
See 1 more Smart Citation
“…30 A significantly lower value in Chroma Meter reading was measured in patients with untreated AD after 10 hours compared with that seen at time point zero, indicating a significant dye penetration caused by a disrupted outside-inside barrier. Dye penetration was significantly reduced by betamethasone and even more so by pimecrolimus treatment compared with that seen in untreated control skin.…”
Section: Tewl and Dye Penetrationmentioning
confidence: 82%
“…Measurements (b*-mode) were taken 15 minutes after application (for drying of the dye) and after 10 hours. 30 Color intensity decreased according to the penetration of the dye into the skin.…”
Section: Dye Penetrationmentioning
confidence: 99%
“…For example, it has been shown that the penetration of polyethylene glycol or sodium laurylsulfate is increased in atopic dermatitis (92). Measurements of skin penetration are often difficult to perform because the compound which penetrated into the skin must be detected by chemical analysis in tape‐stripped material, biopsies, through radioactive labelling, which can no longer be performed in humans, or by the penetration of dyes which can be traced with devices like the Chromameter ® (Minolta, Osaka, Japan) (93).…”
Section: Determination Of Skin Barrier Functionmentioning
confidence: 99%
“…A grande maioria dos ensaios clínicos (10)(11)(12)(13)(14)(15)(16) foi realizado nos Estados Unidos, um estudo (17) foi realizado na Bélgica e outro na França (28) .…”
Section: Métodosunclassified
“…A maioria dos ensaios clínicos foi realizada com crianças (10,12,14) e três estudos foram conduzidos com adultos e crianças (13,15,17) . Uma pesquisa (16) teve sua amostra composta de mulheres adultas e somente três ensaios clínicos (11,18,28) foram realizados com idosos estudando o problema da dermatite associada à incontinência.…”
Section: Métodosunclassified